PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR PKn SISWA KELAS IVA SD NEGERI 035 SEKELADI KECAMATAN TANAH PUTIH - Juneni Juneni; Zulkifli Zulkifli; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : this Research have go to to to level it result study class student PKn IV A SDN 035 Soil Sekeladi White with student's number sebanya 20 student's people. this Research is done with 2 cycle, every cycle consist from 2 time meeting with 1 time repeating of daily. data Instrument collection to research this is teacher's observation sheet, student's observation sheet and result test study.The activity data analysiical-Result teacher to cycle meeting I first 65,63 % and second meeting to level become 68,75 %. To cycle meeting II first 78.13% and second meeting to level become 86,00%. Next the activity data analysiical-result student to cycle meeting I first 67,50% and second meeting to level become 72,50%. To cycle meeting II first 77,50% and second meeting to level become 84,00%. From this research result be obtained result study student to undergo leveling that is average result study student to base skor is 69,75 to level to cycle I become 79,50 to level again to cycle II 80,75. To completing study to base skor is 9 people ( 45 % ) to level to cycle I become 14 people ( 70 % ) and to level again to cycle II become 19 people ( 95 % ). With such can to be concluded that to be applied the Cooperative Studying Model Type Two Stay Two Stray ( TSTS) can to level it result study class student PKn IVA SDN 035 Soil Sekeladi White.Key Word : Studying Model Two Stay Two Stray ( TSTS) , studying Result PKn.